Physiological, biochemical and molecular changes occurring during olive development and ripening - Conde, Carlos (Journal of plant physiology, 2008)
Since ancient times the olive tree (Olea europaea), an evergreen drought- and moderately salt-tolerant species, has been cultivated for its oil and fruit in the Mediterranean basin. Olive is unique among the commercial important oil crops for many reasons. Today, it ranks sixth in the world's production of vegetable oils. Due to its nutritional quality, olive oil has a high commercial value compared with most other plant oils. Olive oil has a well-balanced composition of fatty acids, with small amounts of palmitate, and it is highly enriched in the moneonic acid oleate. This makes it both fairly stable against auto-oxidation and suitable for human health. Nevertheless, it is the presence of minor components, in particular phenolics, contributing for oil's high oxidative stability, color and flavor, that makes olive oil unique among other oils. Moreover, as a result of their demonstrated roles in the prevention of cancer and cardiovascular diseases, olive phenolics have gained much attention during the past years. Also unique to virgin olive oil is its characteristic aroma. This results from the formation of volatile compounds, namely, aldehydes and alcohols of six carbon atoms, which is triggered when olives are crushed during the process of oil extraction. The biochemistry of the olive tree is also singular. O. europaea is one of the few species able to synthesize both polyols (mannitol) and oligosaccharides (raffinose and stachyose) as the final products of the photosynthetic CO(2) fixation in the leaf. These carbohydrates, together with sucrose, can be exported from leaves to fruits to fulfill cellular metabolic requirements and act as precursors to oil synthesis. Additionally, developing olives contain active chloroplasts capable of fixing CO(2) and thus contributing to the carbon economy of the fruit. The overall quality of table olives and olive oil is influenced by the fruit ripening stage. Olive fruit ripening is a combination of physiological and biochemical changes influenced by several environmental and cultural conditions, even if most events are under strict genetic control